SILENCE IS GOLDEN: PUTTING YOURSELF IN THE PATIENTS' SHOES - Alessandra Soares Queiroz; Bruna de Abreu Porciúncula; Marina Ramos Baeta Neves; Natália Carneiro de Freitas; Rafaela Vieiralves João Izzo Pinto; Sergio Zaidhaft (Escola Bahiana de Medicina e Saúde Pública, 2017)
In order to develop empathy for patients and to have a better understanding of theirlimitations and difficulties of compliance to prescriptions and proscriptions, theDoctor-Patient Relationship discipline of a Brazilian medical school asks itsstudents to feel, for a certain time, the restrictions imposed by some disease orcondition. Five female students, self-defined as extremely talkative, remained silent for two days. An individual report was made, and the experience of all was checked in regards to: the motivation and the expectations for the work; the reaction of relatives, teachers and colleagues; the feelings and reflections provided by the experience.